PELAKSANAAN 7 KONTAK ASI PADA KEBERHASILAN MENYUSUI - Febriani, Anggy; Wisuda Andeka Marleni, Kamsiah, (Politeknik Kesehatan Kemenkes Bengkulu, 2018)
The success of implementing Exclusive Breastfeeding is influenced by several factors.To achieve successful breastfeeding, the WHO has established the existence 7 ASI Contact withlactation counselor or lactation clinic. The purpose of this study was to determine the analysis ofthe implementation of the 7 ASI contact to successful breastfeeding in the working area of UPTDPuskesmas Pasar Ikan Bengkulu City of Year 2017. This study design using analytic survey withcross sectional approach. Total sample of 66 mothers breastfeeding > 6 months.sampling usingtechniques consecutive sampling and data analysis using statistical test Chi-Square. The resultsshowed 66 mothers breastfeeding > 6 months, most mothers have carried out 7 ASI contacts andsuccessfully breastfeed exclusively (77.2%). Test results Chi-Square show that there was arelationship implementation 7 ASI contacts to successful breastfeeding in the working area ofUPTD Puskesmas Lingkar Barat Bengkulu City of Year 2017 (ρ=0.000,OR = 7.088). The resultsof this study demonstrated an association implementation of the 7 ASI contact ASI to successfulbreastfeeding because 7 ASI contact to affecting successful of breastfeeding.